2012
DOI: 10.1093/ndt/gfs292
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin increases S261 phosphorylation in AQP2-P262L, a mutant in recessive nephrogenic diabetes insipidus

Abstract: Background. Mutations in the aquaporin-2 (AQP2) gene cause nephrogenic diabetes insipidus (NDI), a renal disorder characterized by polyuria due to a lacking antidiuretic response to vasopressin. While most AQP2 mutants in recessive NDI are misfolded and retained in the endoplasmic reticulum, AQP2-P262L in NDI was impaired in its vasopressin-dependent translocation from vesicles to the plasma membrane. Methods. Vasopressin-induced translocation of AQP2 coincides with AQP2 phosphorylation at S256, S264 and T269 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…Because 4AD inhibits only the S256 phosphorylation, our data corroborate the many earlier studies in providing further evidence that the S256 phosphorylation is the crucial trigger for the membrane insertion of AQP2. [7][8][9]15,25 Our data also show that the cAMP-dependent dephosphorylation at S261 and the phosphorylation at S269 are independent from the S256 phosphorylation by PKA. Tamma et al found that the cAMP/PKA-dependent S261 phosphorylation also occurs in the AQP2-S256A mutant, which cannot be phosphorylated at S256, and that forskolin induces dephosphorylation of S261 in this mutant.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Because 4AD inhibits only the S256 phosphorylation, our data corroborate the many earlier studies in providing further evidence that the S256 phosphorylation is the crucial trigger for the membrane insertion of AQP2. [7][8][9]15,25 Our data also show that the cAMP-dependent dephosphorylation at S261 and the phosphorylation at S269 are independent from the S256 phosphorylation by PKA. Tamma et al found that the cAMP/PKA-dependent S261 phosphorylation also occurs in the AQP2-S256A mutant, which cannot be phosphorylated at S256, and that forskolin induces dephosphorylation of S261 in this mutant.…”
Section: Discussionsupporting
confidence: 70%
“…In line with these observations, 4AD prevented the forskolin-induced increase of AQP2 phosphorylation at S256 (AQP2-pS256) and S269 (AQP2-pS269) at the plasma membrane ( Figure 3). The reason for the nuclear staining with the anti-pS269 antibody in the absence of forskolin is unclear; it also occurred with a custom-made antibody 25 (data not shown), suggesting that the antibodies cross-react with a nuclear protein containing a similar epitope. The effective concentrations of 4AD did not induce any visible signs of toxicity in MCD4 or IMCD cells (24-hour toxicity assay) (Supplemental Figure 3B).…”
Section: Ad Prevents the Camp-induced Redistribution Of Aqp2mentioning
confidence: 99%
See 2 more Smart Citations
“…AQP2-pS256 antibodies were a kind gift from Peter Deen (Department of Physiology, Radboud University Medical Center, Nijmegen, The Netherlands) and has been described previously (Trimpert et al, 2012). AQP2-pS261 antibodies were purchased from Novus Biological (DBA, Milan, Italy).…”
Section: Antibodiesmentioning
confidence: 99%